1987
DOI: 10.1897/1552-8618(1987)6[793:efroft]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Endpoints for Responses of Fish to Chronic Toxic Exposures

Abstract: The concept of chronic toxicity has caused confusion in fish toxicology because it has developed four connotations: long duration, inclusion of all life stages, low severity, and high sensitivity. To compare alternate chronic tests and expressions of test results, we extracted concentration‐response data from published life‐cycle, partial‐life‐cycle, and early life‐stage tests and derived concentration‐response relationships by nonlinear regression. The effects examined were reductions in parental survival, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 13 publications
3
62
0
Order By: Relevance
“…They concluded that the shortcomings of the NOEC provide an incentive to develop model-based methods for expressing the relationship between concentration and effect. Barnthouse et al (1987) and Suter et al (1987) both commented on the fact that 'large' effects may be present at 'safe' concentrations. This is a direct consequence of the statistical power of the testing procedures.…”
Section: A Review Of the Scientific Literaturementioning
confidence: 99%
“…They concluded that the shortcomings of the NOEC provide an incentive to develop model-based methods for expressing the relationship between concentration and effect. Barnthouse et al (1987) and Suter et al (1987) both commented on the fact that 'large' effects may be present at 'safe' concentrations. This is a direct consequence of the statistical power of the testing procedures.…”
Section: A Review Of the Scientific Literaturementioning
confidence: 99%
“…The ability to successfully reproduce is essential for the establishment and continued maintenance of viable fish populations. In addition, certain reproductive processes, including egg production (Suter et al 1987) and embryonic development (Adams and Greeley 1993) …”
Section: Bioindicators Of Reproductive Competence (Subtask 3b)mentioning
confidence: 99%
“…The Chronic National Ambient Water Quality Criteria (NAWQC) for Protection of Aquatic Life are based on thresholds for statistically significant effects on individual responses of fish and aquatic invertebrates. Those thresholds correspond to approximately 25% reductions in the parameters of fish chronic tests (Suter et al 1987). Because of the compounding of individual responses across life stages, the chronic NAWQC frequently correspond to much more than 20% effects on a continuously-exposed fish population (Barnthouse et al 1990).…”
Section: Selection Of Levels Of Effect On Properties Of Endpoint Entimentioning
confidence: 99%